Difference between Nutrition Status in First and Recurrent Ischemic Stroke Patients: a Retrospective Cross-Sectional Study - Amalia, Lisda; Khairunnisa, Shafa Ayu (Global Medical & Health Communication (GMHC), 2023)
Malnutrition in stroke patients can be caused by neurological deficits such as decreased consciousness, dysphagia, cranial nerve paresis, and hemiparesis/hemiplegia. The condition of malnutrition seriously impacts healing and can exacerbate the underlying disease, in this case, stroke, so malnutrition in stroke patients extends the length of stay and increases morbidity and mortality. This study compares nutritional status between first and recurrent ischemic stroke patients based on body mass index (BMI) and subjective global assessment (SGA). This study is a comparative analysis of the medical records of ischemic stroke patients in Dr. Hasan Sadikin General Hospital Bandung from January 2018 until December 2020. The chi-square and Fisher's exact tests were used for statistical analysis. The significance criteria are the p-value if p≤0.05 means statistically significant. A total of 236 subjects in both groups of first and recurrent ischemic stroke patients consisting of 130 men and 106 women with an average age of 56.64 and 61.75 years, and the majority had risk factors for hypertension. The first ischemic stroke group has a good nutrition status compared with the recurrent stroke group (p<0.05). Thirteen patients (11.02%) of first ischemic stroke and 11 patients of recurrent ischemic stroke (9.32%) were underweight, 67 patients (56.78%) of first ischemic stroke and 74 patients of recurrent ischemic stroke (62.71%) had average weight, 31 patients (26.27%) first ischemic stroke and 33 patients (27.97%) recurrent ischemic stroke were overweight, five patients (4.24%) first ischemic stroke and seven patients (5.93%) recurrent ischemic stroke were obese (p<0.05). In conclusion, there was a significant difference in the nutritional status of first and repeated ischemic stroke patients. The nutritional status of recurrent ischemic stroke patients is worse than that of first ischemic stroke patients.